Intervention Nursing In Wound Care: A Literature Study - susyfitrianingsih; Putri Septina; Rahmadani Fitria; Yulfitriana Amir (CV. AFDIFAL MAJU BERKAH, 2026)
Wound care is an essential part of nursing practice aimed at accelerating healing, preventing infection, and improving the patient's quality of life. This literature study aims to analyze various effective nursing interventions in wound care based on current empirical evidence. The method of this literature study uses a systematic approach by searching for articles from the ScienceDirect, PubMed, and Google Scholar databases for the period 2019–2025. Methodological quality assessment was conducted using the Joanna Briggs Institute (JBI) Critical Appraisal Tool. A total of 10 selected articles show that interventions such as modern dressings (foam, hydrogel, honey dressing), patient education, and evidence-based wound care practice are proven to improve the healing process and reduce infection complications. In conclusion, integrated nursing interventions, including the use of modern dressings and patient education, are effective in improving clinical outcomes and accelerating wound healing.